(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1855)
The author gives an account of the Cathedral church at Rosemarkie and its connection to the Italian saint St. Boniface. The discussion covers the history of the church building and in particularly the decorations on the church. The article concludes with a description of the contents of a tomb assumed to belong to a bishop. Members were able to view some lithographs of the church’s decoration and examples of the silks that were removed from the tomb.